Glial Cells: Role of the Immune Response in Ischemic Stroke - Xu, Shenbin; Lu, Jianan; Shao, Anwen; Zhang, John H.; Zhang, Jianmin (Frontiers in Immunology, 2020)
Ischemic stroke, which accounts for 75–80% of all strokes, is the predominant cause of morbidity and mortality worldwide. The post-stroke immune response has recently emerged as a new breakthrough target in the treatment strategy for ischemic stroke. Glial cells, including microglia, astrocytes, and oligodendrocytes, are the primary components of the peri-infarct environment in the central nervous system (CNS) and have been implicated in post-stroke immune regulation. However, increasing evidence suggests that glial cells exert beneficial and detrimental effects during ischemic stroke. Microglia, which survey CNS homeostasis and regulate innate immune responses, are rapidly activated after ischemic stroke. Activated microglia release inflammatory cytokines that induce neuronal tissue injury. By contrast, anti-inflammatory cytokines and neurotrophic factors secreted by alternatively activated microglia are beneficial for recovery after ischemic stroke. Astrocyte activation and reactive gliosis in ischemic stroke contribute to limiting brain injury and re-establishing CNS homeostasis. However, glial scarring hinders neuronal reconnection and extension. Neuroinflammation affects the demyelination and remyelination of oligodendrocytes. Myelin-associated antigens released from oligodendrocytes activate peripheral T cells, thereby resulting in the autoimmune response. Oligodendrocyte precursor cells, which can differentiate into oligodendrocytes, follow an ischemic stroke and may result in functional recovery. Herein, we discuss the mechanisms of post-stroke immune regulation mediated by glial cells and the interaction between glial cells and neurons. In addition, we describe the potential roles of various glial cells at different stages of ischemic stroke and discuss future intervention targets.